Prospects of Antiangiogenic Therapy for Portal Hypertension in Liver Cirrhosis - D. V. Garbuzenko (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
Aim. This paper is aimed at reviewing existing literature that investigates the role of angiogenesis in portal hypertension pathogenesis in liver cirrhosis and the possibilities of its antiangiogenic therapy, along with the description of angiogenesis inhibiting drugs and their action mechanisms.Key points. A relevant literature and reference list search was performed using PubMed and RSCI and Google Scholar, and covered the 2000–2017 period. The following keywords were used: liver cirrhosis, portal hypertension, pathogenesis, angiogenesis, antiangiogenic therapy. The inclusion criteria were limited to the antiangiogenic therapy of portal hypertension. Angiogenesis is shown to play an important role in the pathogenesis of liver cirrhosis. Angiogenesis is the basis for the development of associated portal hypertension that causes its characteristic complications. The experimental studies reviewed in this paper investigate the action mechanism of angiogenesis inhibiting drugs and their effect on portal hypertension. It is shown that, so far, only tyrosine kinase inhibitors have been tested in patients with liver cirrhosis as an antiangiogenic therapy for portal hypertension. Conclusion. Antiangiogenic therapy, selectively directed at unusually growing newly-formed vessels, can be a pathogenetically justified method for treating portal hypertension in liver cirrhosis on its subclinical stage.